Education Quality Assurance Management in the Faculty of Health Science, Singaperbangsa Karawang University - Ruslan Wahyudin, Undang; Permana, Hinggil (KnE Social Sciences, 2020)
This research was conducted at the Faculty of Health Sciences, Singaperbangsa Karawang University, and aims to describe the depth of Education Quality Management at the Faculty with a focus on planning, organizing, and monitoring. The research method used is qualitative with descriptive methods. Data was collected through observation, interviews, and documentation studies. Sources of data came from several key informants, namely the Gugus Jaminan Mutu (GJM), the Gugus Kendali Mutu (GKM) and the Badan Penjaminan Mutu (BPM). The results of this study indicate planning should include analysis of the needs of each study program with communication, consultation and coordination, building teams, evaluating and revising quality standards on an ongoing basis in the implementation of activities which are then approved by the Vice Dean I. The next step is organizing the process by reviewing the rules, determining the organizational structure and job descriptions, asking each study program to determine and assign personnel. Finally, supervision requires the implementation of the academic quality assurance system and the evaluation of this system via various measures. Keywords: quality management, planning, supervision